A bibliometric analysis of research on acoustic emission for nondestructive testing - Yan, Yu; Yang, Zhensheng; Li, Haoda; Jiang, Chenming (IOP conference series. Materials Science and Engineering, 2021)
Acoustic emission (AE) testing has been an active area of research globally for many decades. The present work is a comprehensive overview based on bibliometric analysis to investigate the application of AE research. The publication trends, key areas, organizations, countries, and sources and publications of AE applications are presented to address the following basic questions: what are the publication sources and trends, what are the key areas, and which countries and organizations are active in AE research? The influences of various AE subjects and topics are also discussed. With the help of the Web of Science Core Collection database and the specialized bibliometric analysis tool VOSviewer, the results are visualized properly, and it is found that AE research is currently developing rapidly.